Involvement of SIK2 in FGF2 signal regulation via RAF-1 and generation of mutants for identification of phosphorylation sites on SIK2 by ERK - Akay, Özden. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
Müller cell proliferation is induced by FGF2 signaling via Ras/MAPK pathway through rapid and transient ERK1/2 activation. Salt inducible kinase 2 (SIK2), a serine/threonine kinase, is a novel regulator in this context. Results from our laboratory implicate SIK2 in downregulation of FGF2 signaling through phosphorylation of adaptor protein, Gab1 on Ser266. SIK2 also phosphorylates another pathway element, Raf-1 on Ser621. In this study, we hypotesized that SIK2 phosphorylation of Raf-1 downregulates its activity and activation of downstream elements in FGF2 signaling. In this context modulation of Raf-1 phosphorylation on Ser621 was investigated in FGF2 treated control and SIK2 silenced Müller cells in a time course from 0 to 120 minutes. Raf-1 activity was analyzed by in vitro kinase assay using kinase inactive MEK as Raf-1 substrate. Our data revealed that Raf-1 phosphorylation on Ser621 reaches maximum level at 10 minutes and the minimum level at 60 minutes of FGF2 treatment. Raf-1 activity is the highest in SIK2 silenced cells at 10 minutes and close to basal level at 60 minutes. These data are in accordance with SIK2 activation profile. It can be concluded that SIK2 inhibits Raf-1 activity by phosphorylating it on Ser621 at 10 minutes when SIK2 has the maximum activity. Raf-1 phosphorylation status and activity approximates to basal levels at 60 minutes where SIK2 activity is at minimum level. In the second part of the study, phosphorylation of SIK2 by ERK was investigated through generation of SIK2 mutants. Our previous data shows that ERK phosphorylates SIK2 on two candidate threonines as 758 and 863 based on ERK phosphorylation motif, (S/T)P adjacent to FxFP motif (DED domain). This phosphorylation results in activation and modulation of SIK2. As a first step in identification of target residues, T863A SIK2 mutant was generated.
Keywords: Protein kinases.; Fibroblast growth factors.; Phosphorylation.